Are There Atheists in Foxholes?: Combat Intensity and Religious Behavior - Wansink, Brian (Journal of religion and health, 2013)
After battle, the moral and mortality stresses influence different soldiers in different ways. Using two large-scale surveys of World War II veterans, this research investigates the impact of combat on religiosity. Study 1 shows that as combat became more frightening, the percentage of soldiers who reported praying rose from 42 to 72 %. Study 2 shows that 50 years later, many soldiers still exhibited religious behavior, but it varied by their war experience. Soldiers who faced heavy combat (vs. no combat) attended church 21 % more often if they claimed their war experience was negative, but those who claimed their experience was positive attended 26 % less often. The more a combat veteran disliked the war, the more religious they were 50 years later. While implications for counselors, clergy, support groups, and health practitioners are outlined, saying there are no atheists in foxholes may be less of an argument against atheism than it is against foxholes.